Indirect-to-Direct Band Gap Transition of Si Nanosheets: Effect of Biaxial Strain - Kim, Byung-Hyun; Park, Mina; Kim, Gyubong; Hermansson, Kersti; Broqvist, Peter; Choi, Heon-Jin; Lee, Kwang-Ryeol (American Chemical Society, 2018)
The effect of biaxial strain on the band structure of two-dimensional silicon nanosheets (Si NSs) with (111), (110), and (001) exposed surfaces was investigated by means of density functional theory calculations. For all the considered Si NSs, an indirect-to-direct band gap transition occurs as the lateral dimensions of Si NSs increase; that is, increasing lateral biaxial strain from compressive to tensile always enhances the direct band gap characteristics. Further analysis revealed the mechanism of the transition which is caused by preferential shifts of the conduction band edge at a specific k-point because of their bond characteristics. Our results explain a photoluminescence result of the (111) Si NSs [U. Kim et al., ACS Nano 2011,.5, 2176-2181] in terms of the plausible tensile strain imposed in the unoxidized inner layer by surface oxidation.
Keywords: SILICON NANOSHEETS; MOLECULAR-DYNAMICS; LIGHT; NANOWIRES; NANOSTRUCTURES